THE INFLUENCE OF AI USAGE AND DIGITAL INFORMAL LEARNING IN ENHANCING ISLAMIC TEACHER’S EFFECTIVENESS IN SOUTHERN PAKISTAN - Muhammad Kashif Majeed (LINGUAMEDIA Journal, 2025)
At the time, when the world is going through the period of accelerated technological development, the instructional effectiveness of teachers is very important to satisfy the requirements of the modern education, especially in the context of the linguistic and culturally diverse environment. Digital informal learning and Artificial Intelligence (AI) have become the disruptive tools to help teachers enhance their teaching activities, in particular, in the under-resourced schools. Although interest in the AI-based education is increasing, few studies have examined the combination of AI tools and digital informal learning to enhance the overall effectiveness of instruction among teachers in the Islamic secondary schools of Southern Pakistan. This quantitative research question is how AI tools can enhance English language proficiency, how digital informal learning can enhance cultural awareness, and how the two can enhance the instructional effectiveness of teachers. The survey of 450 Islamic secondary school teachers was conducted with the use of a purposive sample and the survey was carried out with the help of a structured questionnaire using SPSS (2021) with descriptive statistics and independent sample t -tests. The results indicate that AI solutions can significantly improve English language proficiency that is important in effective teaching, whereas digital informal learning helps to develop cultural awareness, allowing educators to work with different learners. These tools are combined, and they have a positive influence on the effectiveness of instruction, increasing the quality of lesson delivery, student behaviour, and classroom management. The research provides the education policy recommendation to incorporate AI and digital tools in teacher training programs, which provides an insight to policymakers and education leaders and developers of EdTech to empower teachers in linguistically and culturally diverse areas.